Perspectives on phronesis in professional nursing practice - Jenkins, Karen (Nursing philosophy, 2019)
The concept of phronesis is venerable and is experiencing a resurgence in contemporary discourses on professional life. Aristotle’s notion of phronesis involves reasoning and action based on ethical ideals oriented towards the human good. For Aristotle, humans possess the desire to do what is best for human flourishing, and to do so according to the application of virtues. Within health care, the pervasiveness of economic agendas, technological approaches and managerialism create conditions in which human relationships and moral reasoning are becoming increasingly de-valued. This creates a tension for nurses, and nursing leaders, as the desire to do what is morally right is often in conflict with contextual demands. In this paper, Aristotle’s writing on phronesis is examined with a focus on his classic conceptions of eudaimonia, the virtues, deliberation, judgement, and praxis. Building on Aristotle’s work, a number of contemporary views are explored with a focus on what various conceptualizations offer for the discipline of nursing. These expanded conceptions of phronesis include attention to: embodiment in practice; open-mindedness including the capacity to stay curious and open to recognizing what we do not know; perceptiveness as a disposition towards insight and aesthetic understanding; and reflexivity as an ongoing process of interrogation and inquiry into ourselves and our actions. Drawing on these concepts, we discuss the affordances of phronesis as a morally informed guiding force to attend to modern-day challenges in nursing practice and nursing leadership.